Multifactorial Predictors of Stunting Among Children Under Five Years: Evidence from Batanghari District, Jambi, Indonesia - Huntari Harahap; Armaidi Darmawan; Anggelia Puspasari; Esa Indah Ayudia; I Made Dwi Mertha Adnyana; Asrica Fitri Yonera; Nurul Uswatun Hasanah (Media Publikasi Cendekia Indonesia, 2026)
Stunting is a public health problem with a high prevalence in Indonesia. The Batanghari District has a stunting rate of 26.3%, exceeding the national target; however, specific regional determinants have not been comprehensively identified. This study aimed to identify multifactorial predictors of stunting in children under five years in Batanghari District. A cross-sectional study was conducted in Batanghari District from August to October 2024, involving 64 children aged 0–60 months selected through purposive sampling. Data were collected via structured questionnaires, anthropometric measurements via WHO standards, and 24 h dietary assessment food recall. Stunting was defined as a height-for-age z score < -2 SD. For statistical analysis, binary logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). The prevalence of stunting was 70.3% (n=45). Inadequate energy density was the strongest predictor (OR = 11.389; 95% CI: 2.906–44.627; p < 0.001), followed by poor drinking water quality (OR = 8.705; 95% CI: 1.668–45.445; p = 0.004), history of problematic pregnancy (OR = 8.250; 95% CI: 0.799–85.165; p = 0.041), poor type of food (OR = 5.123; 95% CI: 1.449–18.110; p = 0.011), calcium density (OR = 4.242; 95% CI: 1.181–15.234; p = 0.021), income below the regional minimum wage (OR = 3.681; 95% CI: 1.146–11.832; p = 0.025), and authoritarian parenting (OR = 3.523; 95% CI: 1.056–11.762; p = 0.036). These findings suggest that stunting in Batanghari District is associated with a complex interplay of nutritional deficiencies, socioeconomic factors, environmental conditions, maternal health, and behavioral factors